1995
DOI: 10.1093/infdis/172.2.558
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Evidence of Staphylococcal Toxin Involvement in the Pathogenesis of Kawasaki Disease

Abstract: To detect a causative superantigen and to clarify a possible role for staphylococci in Kawasaki disease (KD), culture supernatants of individual bacterial isolates from 11 acute-stage patients were studied. Toxic shock syndrome toxin-1 (TSST-1) and antibody to TSST-1 and enterotoxins A (SEA), B (SEB), and C (SEC) in acute (mean, day 7) and late convalescent (mean, month 15) sera from 26 patients (12 with coronary artery aneurysms) and 22 age-matched controls were measured. Only 1 of 60 supernatants was mitogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 11 publications
0
38
2
Order By: Relevance
“…Recently, there has been interest in a superantigen etiology of KD based upon possible selective expansion of V␤2 and V␤8 T cell receptor families in peripheral blood in acute KD (4,5); however, other investigators have been unable to confirm this finding (6 -10). Toxic shock syndrome toxin-1 or streptococcal superantigens were proposed to be related etiologically to KD based upon a single study (11) that has not been confirmed by others (7,8,(12)(13)(14).…”
mentioning
confidence: 99%
“…Recently, there has been interest in a superantigen etiology of KD based upon possible selective expansion of V␤2 and V␤8 T cell receptor families in peripheral blood in acute KD (4,5); however, other investigators have been unable to confirm this finding (6 -10). Toxic shock syndrome toxin-1 or streptococcal superantigens were proposed to be related etiologically to KD based upon a single study (11) that has not been confirmed by others (7,8,(12)(13)(14).…”
mentioning
confidence: 99%
“…Of particular note in the present studies, we surveyed kinetic changes of IgM responses, which were not affected by IVIG treatment. To our knowledge, there has been only one report dealing with IgM antibodies against SAgs by Terai et al [10], who showed no evidence of significant elevation of anti-TSST-1 IgM antibodies. However, their studies set cut-off levels based on adult volunteers, and examined IgM antibody against only one SAg, i.e.…”
Section: Discussionmentioning
confidence: 90%
“…The involvement of SAgs in KD has been investigated by a variety of methods such as isolation of SAg-producing pathogens [6,8,9], selective expansion of TCR Vβ-bearing T cells in peripheral blood [3][4][5]7], and serological immune responses [10][11][12][13][14]. However, exogenous administration of immunoglobulin products can potentially limit the ability to accurately evaluate IgG responses to SAgs in KD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Efforts to identify the KD superantigen, including attempts to implicate TSST-1 as the cause, have been unrewarding. 27,28 The importance of this to the emergency physician is to realize the blurred clinical and immunologic lines that separate these diseases. The possibility that TSS and KD may occur simultaneously makes it necessary to consider instituting treatment for both diseases in certain case scenarios, as in the one presented.…”
Section: Resident Discussionmentioning
confidence: 99%